TANTANGAN DAN ANCAMAN ANAK INDONESIA: POTRET PENDIDIKAN NASIONAL ERA DIGITAL - Firman Mansir (Universitas PGRI Semarang, 2022)
AbstractThis article describes the various challenges and threats experienced by children in educational institutions, especially in schools. This study aims to identify and explain the concept and framework of challenges and threats faced by Indonesian children. In Indonesia, there are still many challenges and threats for children to be able to grow and develop without any obstacles. Like many cases happen involving children. This can affect physical and psychological health. The role of government, family and society is very important in protecting children and this issue should be a focus of attention that cannot be ruled out. This study uses a qualitative approach. So that in collecting data through literature analysis sourced from national and international journal articles and research books that are in line with the topic of discussion. Thus, related to the underlying causes of threats to Indonesian children in schools in the perspective of National Education. There is a response through various educational political policies that can be followed by all components and the education community. The position of Indonesian children is a valuable asset that must be maintained in order to realize the ideals of the nation.Keywords: Child Education, National Education, IndonesiaAbstrakArtikel ini menjelaskan tentang berbagai tantangan dan ancaman yang dialami pada anak di lembaga pendidikan khususnya di sekolah. Penelitian ini bertujuan untuk mengetahui dan menjelaskan konsep dan kerangka tantangan dan ancaman yang dihadapi oleh anak Indonesia. Di Indonesia masih banyak tantangan dan ancaman bagi anak untuk dapat bertumbuh dan berkembang tanpa adanya hambatan. Seperti banyak kasus terjadi yang melibatkan anak-anak. Hal tersebut dapat berpengaruh pada kesehatan fisik maupun psikis. Peran pemerintah, keluarga dan masyarakat sangat berarti terhadap perlindungan anak dan seharusnya masalah ini harus menjadi fokus perhatian yang tidak bisa dikesampingkan. Penelitian ini menggunakan pendekatan kualitatif, sehingga dalam mengumpulkan data melalui analisis literatur yang bersumber dari artikel jurnal nasional dan internasional serta buku hasil penelitian yang searah dengan topik pembahasan. Dengan demikian, terkait peyebab yang mendasari ancaman pada anak Indonesia di sekolah dalam perspektif Pendidikan Nasional mendapat respon melalui berbagai kebijakan politik pendidikan yang bisa diikuti oleh semua komponen dan masyarakat pendidikan. Kedudukan anak Indonesia merupakan aset beharga yang harus dijaga agar dapat mewujudkan cita-cita bangsa.Kata kunci: Pendidikan Anak, Pendidikan Nasional, Indonesia